THE IMPORTANCE OF POLYPHENOLS IN THE PREVENTION OF CHRONIC NON-COMMUNICABLE DISEASES - Jandric-Kocic, Marijana (HEALTH CARE, 2021)
Polyphenols are compounds that contain in their structure one or more hydroxyl groups attached directly to one or more aromatic hydrocarbons. They represent one of the most numerous and widespread groups of secondary plant metabolites with more than 8000 polyphenolic structures. Polyphenols are antioxidants that reduce endothelial dysfunction and blood pressure, improve the immune defense, alleviate the inflammatory response, block platelet aggregation and oxidation of low-density lipoproteins. Some studies suggest that there is an indirect link between flavonoid intake and myocardial infarction and coronary heart disease. Dark chocolate, nuts, grapes, red wine and the Mediterranean diet (based on fruits and vegetables, fish and olive oil) are rich in polyphenols and are key in preventing cardiovascular disease. Polyphenols prevent neurodegenerative changes associated with cerebral ischemia. Blueberry anthocyanins have antiatherogenic and anti-inflammatory properties so they have a neuroprotective effect. Red wine extract, rich in anthocyanin, reduces injuries caused by cerebral ischemia. Food intake of polyphenols can reduce hypertension, anti-inflammatory and antioxidant effects, as well as increased production of nitric oxide. The importance of black and green tea in lowering blood pressure is especially pointed out. Further research on polyphenols is needed in order to make as clear recommendations as possible for their general preventive use.